Human Norovirus Proteins: Implications in the Replicative Cycle, Pathogenesis, and the Host Immune Response - Campillay-Véliz, Claudia P.; Carvajal, Jonatan J.; Avellaneda, Andrea M.; Escobar, Darling; Covián, Camila; Kalergis, Alexis M.; Lay, Margarita K. (Frontiers in Immunology, 2020)
Human noroviruses (HuNoVs) are the cause of more than 95% of epidemic non-bacterial gastroenteritis worldwide, with some lethal cases. These viral agents affect people of all ages. However, young children and older adults are the highest-risk groups, being affected with the greatest rate of hospitalizations and morbidity cases. HuNoV structural proteins, especially VP1, have been studied extensively. In contrast, the functions of the non-structural proteins of the virus have been undescribed in depth. The study of the HuNoV non-structural proteins have mostly been made by expressing them individually in in vitro cultures, providing insights in their functions and role that play in HuNoV replication and pathogenesis. This review examines exhaustively the functions of both HuNoV structural and non-structural proteins and their possible role within the viral replicative cycle and pathogenesis of the virus. It is also highlighted recent findings regarding the host's innate and adaptive immune responses against HuNoV, which are of great relevance for diagnostics and vaccine development to prevent infections caused by these fastidious viruses.